Toradora!. 1 - Takemiya, Yuyuko, 1978-; Sullivan, J. P (Seven Seas Entertainment, LLC, 2018)
Takasu Ryuuji, who has an uninentionally scary face, finds it difficult to meet girls, until he crosses paths with Aisaka Taiga, whose frightening demeanor makes up for her diminutive stature.